The Climate elements impact upon the expansion the stages morphology of Akre city (Raparin Journal of Humanities (RJH), 2024)
The aim this paper is to determine the climate elements factors such as sunlight, temperature, wind, rain and humidity impact on the stages of morphology in Akre and the development and expansion of this city under the influence of climate. The parts of the city, and the climate elements have played a significant role in the formation of morphology in Aker, and the characteristics of the climate have a direct and positive relationship with the planning and stages of morphology in Akre, and some parts of Akre, and Suitable for the climatic situation of the place.The study also includes a field visit to receive more and analyze the composition of Akre, the research consists of the first topic expansion in morphology of Akre, the second topic of the current structure and the future of the city, and the third topic climate elements impact on the morphology of akre, with some conclusion and suggestion.